Henryka Jakubanisa (1879-1949) kijowski okres życia i twórczości historycznofilozoficznej = Henryk Jakubanis (1879-1949) Kyiv period of life and historical-philosophical work - Sargsyan, Mariam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Henryk Jakubanis (1879-1949) was a researcher of antiquity, a philosopher and a historian of ancient philosophy. He was born in central Russia to a Polish family of Lithuanian origin. The intellectual biography of this researcher is usually divided into two periods: Kyiv (1897-1922) and Lublin (1922-1949). The Lublin period is quite well studied by Polish authors, while the importance of the Kyiv period of this historian of philosophy remains unclear. The aim of the article is to present the life and academic activity of H. Jakubanis in the Kyiv period.
Keywords: Jakubanis, Henryk (1879-1949); history of Polish philosophy; the Saint Vladimir Imperial University of Kyiv; Gilarow, Aleksiej (1856-1938); filozofia polska - historia; Kijowski Uniwersytet św. Włodzimierza